Effects of NaCl substitution by KCI on the sensory and physico-chemical characteristics of surimi-based fish sauages. - Senangote, Rheane Joy Esponilla
Cardio-vascular diseases (CVD) are the l; leading cause of mortalities worldwide with high blood pressure as the most rampant major risk factor. One of the strategies to decrease the risk for diet-driven CVD is salt substitution in processed food like surimi-based fish sausages. However, salt (NaCl) is an important ingredient during processing to achieve the desired quality characteristics of the product. In this study, KCL was used as a salt substitute as it has anti-hypertensive properties as opposed to NaCl. Five treatments were devised: T1-2% NaCl (control), T2-1.5% NaCl+0.5% KCL, T3 1% NaCl + 1% KCL; T4- 0.5% NaCl + 1.5% KCL; and T5-2% KCL. Physico-chemical properties, sensory attributes, and acceptability were assessed. There were no significant differences in the textural characteristics of fish sausages in all treatments. The sensory attributes and acceptability scores of T1, T2, and T3 are not significantly different with each other. T4 and T5 have a significantly higher bitter taste and lower saltiness scores resulting to lower consumer acceptability. This study shows that KCL can be used as an effective NaCl substitute, at no more than 50% partial replacement, without compromising product quality and acceptability.